Sources of the performance of manufacturing firms: evidence from Vietnam. Issue 6 (2nd November 2019) - Ngo, Thanh; Le, Tu; Tran, Son H.; Nguyen, Anh; Nguyen, Canh
ABSTRACT: We used stochastic frontier analysis (SFA) to investigate the cost efficiency and productivity of the manufacturing sector in Vietnam from 2010 to 2016 to determine the sources of their performance. Our findings suggest that it is important for the country and its regions to create a competitive environment for the development of their local manufacturing firms. We also found that larger firms, those with a longer history and those that are more export-oriented tend to outperform their counterparts. We suggest that the sampled firms should focus more on research and development and technological implementation to shift towards a capital-intensive state and thus enhance their productivity.